8th international conference on management and rehabilitation of chronic respiratory failure: the long summaries – part 1. Issue 1 (December 2015) - Ambrosino, Nicolino; Casaburi, Richard; Chetta, Alfredo; Clini, Enrico; Donner, Claudio; Dreher, Michael; Goldstein, Roger; Jubran, Amal; Nici, Linda; Owen, Caroline; Rochester, Carolyn; Tobin, Martin; et al.
Abstract This paper summarizes the Part 1 of the proceedings of the 8th International Conference on Management and Rehabilitation of Chronic Respiratory Failure, held in Pescara, Italy, on 7 and 8 May, 2015. It summarizes the contributions from numerous experts in the field of chronic respiratory disease and chronic respiratory failure. The outline follows the temporal sequence of presentations. This paper (Part 1) includes sections regarding: Advances in Asthma and COPD Therapy (Novel Therapeutic Targets for Asthma: Proteinases, Blood Biomarker Changes in COPD Patients); The problem of Hospital Re-Admission following Discharge after the COPD Exacerbation (Characteristics of the Hospitalized COPD Patient, Reducing Hospital Readmissions Following COPD Exacerbation).